2022
DOI: 10.1111/ehr.13160
|View full text |Cite
|
Sign up to set email alerts
|

The role of sentiment in the US economy: 1920 to 1934

Abstract: This paper investigates the role of sentiment in the US economy from 1920 to 1934 using digitised articles from The Wall Street Journal. We derive a monthly sentiment index and use a 10-variable vector error correction model to identify sentiment shocks that are orthogonal to fundamentals. We show the timing and strength of these shocks and their resultant effects on the economy using historical decompositions. Intermittent impacts of up to 15 per cent on industrial production, 10 per cent on the S&P 500 and b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 35 publications
0
11
0
Order By: Relevance
“…For example, a plot of relative sentiment against major events in the lead-up to the global financial crisis shows a precipitous decline in relative sentiment in the year leading up to the failure of Bear Sterns in March 2008. A similar analysis using 1920s data from the Wall Street Journal found that sentiment shocks, beyond economic fundamentals, impacted production and stock values leading up to the Great Depression (Kabiri, James, Landon-Lane, Tuckett, & Nyman, 2023); sentiment likewise appears to account for the slow recovery from the 2008 recession (Carlin & Soskice, 2018).…”
Section: Communicationmentioning
confidence: 97%
“…For example, a plot of relative sentiment against major events in the lead-up to the global financial crisis shows a precipitous decline in relative sentiment in the year leading up to the failure of Bear Sterns in March 2008. A similar analysis using 1920s data from the Wall Street Journal found that sentiment shocks, beyond economic fundamentals, impacted production and stock values leading up to the Great Depression (Kabiri, James, Landon-Lane, Tuckett, & Nyman, 2023); sentiment likewise appears to account for the slow recovery from the 2008 recession (Carlin & Soskice, 2018).…”
Section: Communicationmentioning
confidence: 97%
“…That is, they examine how confidence indicators can influence industrial production. Most of the research confirms the relationship in this direction, for example [19][20][21][22][23][24]. An example could be the research carried out in the past in the Euro Area by Cizmesija et al [40], where they concluded on the basis of a regression analysis that, in accordance with changes in confidence indicators, it is possible to predict the direction of changes in industrial production because business survey results are available before the official statistics are published.…”
Section: Discussionmentioning
confidence: 98%
“…The relationship between sentiment-based indexes and industrial production has been proven by several studies [19][20][21]. The study of Arisoy [22] specifically investigated the Business Confidence Indicator and concluded that it does have an impact on important macroeconomic variables including industrial production.…”
Section: Literature Reviewmentioning
confidence: 99%
“…For example, a plot of relative sentiment against major events in the lead-up to the global financial crisis shows a precipitous decline in relative sentiment in the year leading up to the failure of Bear Sterns in March 2008. A similar analysis using 1920s data from the Wall Street Journal found that sentiment shocks, beyond economic fundamentals, impacted production and stock values leading up to the Great Depression (Kabiri, James, Landon-Lane, Tuckett, & Nyman, 2023); sentiment likewise appears to account for the slow recovery from the 2008 recession (Carlin & Soskice, 2018).…”
Section: Shared Narratives Propagate Through Social Networkmentioning
confidence: 94%